Limited Internal Femoral Rotation Increases ACL Strain - Hoyle, Brian (MD Conference Express, 2014)
Limited range of hip internal rotation has been associated with an increased risk for anterior cruciate ligament (ACL) injury, whereby the hips of ACL-injured patients rotated 12.6° less than those of noninjured individuals [Gomes JL et al. Arthroscopy 2008]. This article discusses the underlying mechanism of injury to the ACL associated with decreased internal rotation of the hip.